Pengaruh Peran Suami Terhadap Tingkat Kecemasan Ibu Hamil Dalam Menghadapi Proses Persalinan Di Puskesmas Harapan Raya Pekanbaru - Isnaniar Isnaniar; Wiwik Norlita; Salmi Gusrita (LPPM Universitas Muhammadiyah Riau, 2020)
Labor is the final process of pregnancy that the mother and family have gone through during three trimester periods. When the labor process begins, the mother's role is to give birth to her baby, while the role of the health worker is to monitor childbirth to detect complications early and with the family to provide assistance and support for maternity mothers. The purpose of this study was to provide an effect on the role of the husband on the level of anxiety of pregnant women in dealing with the delivery process at the Harapan raya puskesmas. The research design used in this study was a quantitative descriptive method, at the Harapan Raya Puskesmas Pekanbaru. The population in this study amounted to 40 pregnant women in Harapan Raya Puskesmas Pekanbaru with a sample size of 33 respondents using the Accidental Sampling method. Data collection techniques using questionnaires and data analysis used were univariate and bivariate. Data collection was obtained using a questionnaire, then analyzed using the chi-square test. The results showed a significant influence between the role of the husband with the anxiety level of pregnant women in dealing with the delivery process with a value of p = 0.001. The conclusion is the influence of the role of the husband on the level of anxiety of pregnant women in dealing with the percentage of labor in the Harapan Raya Health Center Pekanbaru there is an influence between the role of your husband and the level of anxiety of pregnant women.hopefully the third trimester pregnant women can pay moor attention to their condition both phisically phisiologically and ask the husband to always provide suppore and particapate in taking care of the pragnancy as walk as in preparing the pragnancy.